Adsorption Kinetics of Pb(II), Cd(II), Zn(II) and Fe(III) onto Saponified Apple Waste - Homagai, Puspa Lal; Paudyal, Hari (Journal of Nepal Chemical Society, 2009)
Saponified apple waste gel was prepared in wet condition with calcium hydroxide at highly alkaline medium. The effect of initial concentration, contact time and pH of the solution was investigated. The maximum adsorption capacity onto this adsorbent was investigated for Fe(III), Cd(II), Zn(II) and Pb(II) at their optimal pH of 3, 6, 4.5 and 3.5 respectively. Langmuir isotherm and pseudo second-order kinetic model gave better explanation of the adsorption process. For binary mixture of Zn(II) and Cd(II), the separation factor and effect on adsorption capacity for both the metals were investigated. Keywords: adsorption, saponified apple waste, bioadsorption. DOI: 10.3126/jncs.v23i0.2103 Journal of Nepal Chemical Society, Vol. 23, 2008/2009 Page: 102-105